PRINCIPLES OF DISCLOSURE AND DIRECTORS' LIABILITY FOR CAPITAL MARKET OFFENCES: PRINCIPLES OF DISCLOSURE AND DIRECTORS' LIABILITY FOR CAPITAL MARKET OFFENCES - Poloan, Khairil; Hasibuan, Fauzie Yusuf; Darodjat, Tubagus Achmad (PENA LAW: International Journal of Law, 2025)
This study aims to analyse the liability of directors for violations of the principle of information disclosure in the Indonesian capital market, with a focus on the implementation of information transparency obligations and the legal impact arising from such violations. This research also examines the application of the principles of Good Corporate Governance (GCG) in information management and the role of organ theory in regulating the responsibility of directors. The results show that violations of the principle of information disclosure can lead to administrative, criminal, and civil sanctions that harm the company's reputation and the integrity of the capital market. In addition, weak GCG implementation in information management increases the risk of violations. This study suggests strengthening regulations and law enforcement related to information disclosure as well as strengthening supervision of the implementation of GCG principles.